INOVASI KEBIJAKAN E-MONEVLAP (ELEKTRONIK MONITORING, EVALUASI DAN PELAPORAN) PADA BAGIAN PROGRAM DESAIN KUALITAS DAN PEMABNGUNAN SEKRETARIAT DAERAH KOTA BANDUNG - Pelangi Bening; Elisa Susanti; Rd Ahmad Buchari (Universitas Padjadjaran, 2022)
This study explains about the City of Bandung in its governance, making policy innovations in the form of an e-Monevlap system (Electronic Monitoring, Evaluation and Reporting) against the background of the low realization of budget absorption in order to accelerate regional development in the City of Bandung which is carried out by the Program, Design and Quality Development Section of the Secretariat Bandung. The purpose of this study is to describe and analyze the implementation of e-Monevlap Policy Innovations (Electronic Monitoring, Evaluation and Reporting in the Design and Quality Development Program Section of the Bandung City Regional Secretariat. The research method used is a qualitative approach. The technique of determining informants uses Purposive Techniques. Researchers use guidance theory A Framework for Analyzing the Implementation of Innovation by Steelman (2010). The results show that the agency has not paid attention to several component factors in implementing e-Monevlap policy innovations, especially on individual factors, structure and culture.From the individual factors in this study the problems that occur caused by the human resources of 74 regional apparatuses in the city of Bandung which have not been maximized in carrying out reporting on budget realization as well as the physical progress of the implementation of each program and activity. From structural factors, it is hampered by policy makers and In this case, the Design and Development Quality Program Division ignores SOPs in the implementation of e-Monevlap and there are no special rules governing the implementation of e-Monevlap, so that this causes e-Monevlap to not be optimal in its implementation. And from the cultural aspect, what is discussed in this factor is the framing component where the policy innovation of the e-Monevlap system cannot solve existing problems, as researchers found that e-Monevlap has not been able to convey to its object, namely the Bandung City regional apparatus, so this implementation still not optimal. Penelitian ini menjelaskan tentang Kota Bandung dalam tata kelola pemerintahan nya membuat Inovasi kebijakan berupa sistem e-Monevlap (Elektronik Monitoring Evaluasi dan Pelaporan) di latarbelakangi rendahnya realiasi penyerapan anggaran guna percepatan pembangunan daerah di Kota Bandung yang dilaksanakan oleh Bagian Program, Desain dan Kualitas Pembangunan Sekretariat Kota Bandung. Tujuan dilakukannya penelitian ini yaitu mendeskripsikan dan menganalisis pelaksanaan Inovasi Kebijakan e-Monevlap (Elektronik Monitoring Evaluasi dan Pelaporan di Bagian Program Desain dan Kualitas Pembangunan Sekretariat Daerah Kota Bandung. Metode Penelitian yang digunakan yaitu pendekatan kualitatif. Teknik penentuan informan menggunakan Teknik Purposive. Peneliti menggunakan guidance theory A Framework for Analyzing the Implementation of Innovation oleh Steelman (2010). Hasil penelitian menunjukkan bahwa instansi belum memperhatikan beberapa komponen faktor dalam melaksanakan inovasi kebijakan e-Monevlap khususnya pada factor individual, struktur dan budaya. Dari factor individual dalam penelitian ini permasalahan yang terjadi disebabkan oleh SDM dari 74 OPD di Kota Bandung yang belum maksimal dalam melaksanakan pelaporan realisasi anggaran serta progress fisik pelaksanaan setiap program dan kegiatan. Dari faktor struktur terhambat disebabkan oleh pembuat kebijakan dalam hal ini Bagian Program Desain dan Kualitas Pembangunan mengabaikan SOP dalam pelaksanaan e-Monevlap juga tidak adanya aturan khusus yang mengatur pada pelaksanaan e-Monevlap, sehingga hal tersebut menyebabkan e-Monevlap belum optimal dalam pelaksanaannya. Dan dari aspek budaya, yang dibahasa dalam faktor ini adalah komponen framing dimana inovasi kebijakan sistem e-Monevlap ini tidak dapat menyelesaikan permasalahan yang ada, seperti yang peneliti temukan e-Monevlap belum mampu tersampaikan pada objek nya yakni OPD Kota Bandung, sehingga pelaksanaan ini masih belum optimal.